Acute Appendicitis in a Man Undergoing Therapy for Mantle Cell Lymphoma - Michael Linden; Ajay Gopal; Kerstin Edlefsen (Case Reports in Hematology)
A 71-year-old man was diagnosed with an aggressive mantle cell lymphoma and was started on six cycles of R-CHOP chemotherapy. Approximately two weeks after starting his first cycle of chemotherapy, he complained of severe right lower quadrant abdominal pain, and an abdominal CT scan demonstrated an enlarged appendix with evidence of contained perforation. The man underwent open appendectomy for acute appendicitis and recovered. The appendectomy specimen was submitted for routine pathological analysis. There was histologic evidence of perforation in association with an inflammatory infiltrate with fibrin adhered to the serosal surface; scattered small lymphoid aggregates were present on the mucosal surface. Although the lymphoid aggregates in the submucosa and lamina propria were rather unremarkable by routine histologic examination, immunohistochemistry revealed the lymphocytes to be predominantly Cyclin D1-overexpressing B cells. To our knowledge, this is the first reported case of acute appendicitis in association with appendiceal involvement by mantle cell lymphoma.